2000
DOI: 10.1111/j.1751-3928.2000.tb00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite/Ilmenite–series Classification and Magnetic Susceptibility of the Mesozoic‐Cenozoic Batholiths in Peru

Abstract: : Plutonic rocks of the Coastal Batholith of Peru were evaluated in terms of the granitoid‐series classification using the bulk ferric/ferrous ratio from the literature and new measurements of magnetic susceptibility. The batholith is largely composed of magnetite‐series plutonic rocks; the magnetite series make up 85% by number of chemical analyses (n=130) and 80% by measurement of magnetic susceptibility (n=210). The ilmenite‐series rocks are mostly found in the felsic facies of the batholith. Asymmetrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…As a whole, the comparison of soil and bedrock data revealed soil χ lf values that were significantly higher (24.1-1193 × 10 −8 m 3 kg −1 ) than those for bedrock (b0.1-18.5 × 10 −8 m 3 kg −1 ). Magnetic χ lf values of the granitic-like bedrocks ranged from 5.33 to 18.5 × 10 −8 m 3 kg −1 , so reflecting data reported in literature for the leucocratic ilmenite series (I-granite), the least magnetic granites (Ishihara, 1977(Ishihara, , 1979Ishihara et al, 2000). In the cases of SPI and SSB, soil χ lf values were enriched vs. bedrock by around 2 orders of magnitude (701-813 vs. 11.9 × 10 −8 m 3 kg −1 and 149-247 vs. 6.28 × 10 −8 m 3 kg −1 ), respectively, while, for CAS, they were generally around 1 order higher (52.6-95.0, solum 1 and 2 respectively, vs. 7.75 × 10 −8 m 3 kg −1 ).…”
Section: Magnetic Susceptibilitysupporting
confidence: 50%
“…As a whole, the comparison of soil and bedrock data revealed soil χ lf values that were significantly higher (24.1-1193 × 10 −8 m 3 kg −1 ) than those for bedrock (b0.1-18.5 × 10 −8 m 3 kg −1 ). Magnetic χ lf values of the granitic-like bedrocks ranged from 5.33 to 18.5 × 10 −8 m 3 kg −1 , so reflecting data reported in literature for the leucocratic ilmenite series (I-granite), the least magnetic granites (Ishihara, 1977(Ishihara, , 1979Ishihara et al, 2000). In the cases of SPI and SSB, soil χ lf values were enriched vs. bedrock by around 2 orders of magnitude (701-813 vs. 11.9 × 10 −8 m 3 kg −1 and 149-247 vs. 6.28 × 10 −8 m 3 kg −1 ), respectively, while, for CAS, they were generally around 1 order higher (52.6-95.0, solum 1 and 2 respectively, vs. 7.75 × 10 −8 m 3 kg −1 ).…”
Section: Magnetic Susceptibilitysupporting
confidence: 50%
“…8 Frost, 2011) as they have FeO tot /(FeO tot + MgO) values of >0.90 and ilmenite-series granites as their magnetic susceptibility values are < 3  -3 SI units (Ishihara et al, 2000) in good agreement with the lack of primary magnetite. Indeed, the magnetic susceptibility values for the pluton range from 20 to 60  10 -6 SI units (Cifelli, pers.…”
Section: Accepted Manuscriptmentioning
confidence: 55%
“…This distribution is at odds with a tectonic model involving a palaeo-subduction zone along the line of the Eastern Palmer Land Shear Zone as this would produce suprasubduction extension and dominantly magnetite-series plutons in the overriding Eastern Domain as well as the volcanic arc of the Central Domain. Instead, the evidence for decreasing fO 2 from west to east supports a simpler model of a single subduction zone west of the Peninsula, placing the magnetite-series granitoids of the Central Domain closer to the convergent margin and the Eastern Domain plutonic rocks farther landward, as seen in North and South America (Ishihara et al 2000;Hart et al 2004). This interpretation of crustal assimilation as the dominant control on magnetic susceptibility is supported by the εNd i data (see above), which show decreased crustal assimilation during formation of the Early Cretaceous extensional magnetite-series intrusions of the Central Domain.…”
Section: Magnetic Susceptibility Of the Magmatic Suitesmentioning
confidence: 95%
“…The distribution of magnetite-series (high fO 2 ) and ilmenite-series (low fO 2 ) granitoids on the East Pacific margin (Ishihara et al 2000;Hart et al 2004) has shown a tectonic control on oxidation state, with dominantly magnetite-series intrusions occurring closest to the convergent margin where crustal extension reduced the degree of crustal contamination and consequent reduction in oxidation state. In contrast, ilmenite-series granitoids dominantly crop out further inland where crustal contamination of the intruding melts was increased by crustal thickening.…”
Section: Magnetic Susceptibility Of the Magmatic Suitesmentioning
confidence: 99%